2014
DOI: 10.1159/000354044
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Oral Health and SES Predictors of Caries in 30-Year-Olds

Abstract: Background/Aims: To assess whether childhood socio-economic status modifies the relationship between childhood caries and young adult oral health. Methods: In 1988-1989, a total of 7,673 South Australian children aged 13 years were sampled, with 4,604 children (60.0%) and 4,476 parents (58.3%) responding. In 2005-2006, 632 baseline study participants responded (43.0% of those traced and living in Adelaide). Results: Adjusted analyses showed significant interactions for card status by DMFT at age 13 for decayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…All of the studies were published between 1975 and 2016 [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Twenty new studies were included in this update [26,27,28,29,31,38,39,40,44,45,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies were published between 1975 and 2016 [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Twenty new studies were included in this update [26,27,28,29,31,38,39,40,44,45,…”
Section: Resultsmentioning
confidence: 99%
“…Twenty new studies were included in this update [26,27,28,29,31,38,39,40,44,45,47,49,50,53,59,61,66,67,79,81]. The language was predominantly English (96.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Visual screening performed by teachers in detection of dental caries has been shown to correlate with clinical dental examination [27]. Previous findings show that caries in the primary dentition are predictive of caries in permanent teeth [28]. Socio economic status (SES), as measured by educational attainment and employment type is associated with oral health of young adults and over the life course.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been reported that SES modified the relationship between child oral health and dental caries at age 30 years [33], with those who were lower SES in childhood being worse off in oral health at age 30 when controlling for differences in childhood caries. This may support social causation explanations for oral health inequalities where SES gradients in health reflect the impact of SES on health through such mechanisms as career prospects and access to goods and services [34].…”
Section: Discussionmentioning
confidence: 99%